Analysis and Optimization of Tooth Surface Contact Parameter of ZC1 Worm Gear - Song Lijuan; Ji Weixi; Xie Jian; Wang Yu (Jixie chuandong)
Based on the meshing theory of ZC1 worm gear pair,the tooth surface contact parameters are analyzed by using MATLAB.The results show that the axial module,center distance,lead angle,radius of arc tooth profile of grinding wheel have great influence on tooth surface contact parameters.In general,the center distance is selected in the beginning of design,so the axial module,lead angle,radius of arc tooth profile of grinding wheel are selected as design variable.For improving the meshing performance of worm gear pair,taking the induced normal curvature and lubrication angle as objective function,and combining with the constraints of top thickness of worm,top thickness of worm wheel and undercutting,the optimum mathematical model is established.The improved particle swarm algorithm is adopted as optimization algorithm and the results show that the optimized lubrication angle is larger and induced normal curvature is smaller.The meshing performance of worm gear pair is improved effectively.